1663. Marked Improvement in Pandemic H1N1 Component Shedding and Immunogenicity in 2017–2018 Russian-Backbone Live Attenuated Influenza Vaccine (LAIV) in Gambian Children. (26th November 2018) - Lindsey, Benjamin; Jankey, Jagne; Armitage, Edwin; Jeffries, David; Mohammed, Nuredin; Drammeh, Sainabou; Senghore, Elina; Sallah, Hadi; Tregoning, John; Hoschler, Katja; Dong, Tao; Clarke, Ed; et al.
Abstract: Background: Recent observational studies in the United States have reported reduced effectiveness of the Ann Arbor-backbone live attenuated influenza vaccine (LAIV), coinciding with emergence of 2009 pandemic H1N1 (pH1N1). A recent RCT in Senegal of the Russian-backbone LAIV also showed no efficacy, with pH1N1 the predominant vaccine-matched strain circulating during the study. The reasons for this reduced effectiveness and efficacy are unclear but may involve pre-existing immunity or pH1N1 virus-specific factors. We explore these underlying reasons through an LAIV immunogenicity study in Gambian children across 2 influenza seasons. Methods: Gambian children aged 24–59 months ( n = 118) were given 2016–17 northern hemisphere Russian-backbone trivalent LAIV. Vaccine shedding, haemagglutinin inhibition (HAI) titre, influenza-specific T-cell responses, and mucosal IgA were measured using RT-PCR, HAI assay, flow cytometry, and ELISA, respectively. The following year, a further 127 children were given 2017–2018 formulation LAIV, where the pH1N1 strain was updated. Results: In 2016–2017, significantly less pH1N1 shedding (13.6% children) was seen compared with H3N2 (45.8%) and B/Victoria (80.5%). Similarly, poor pH1N1-specific HAI (5.1% seroconversion), mucosal IgA (18.6% responders) and T-cell responses (<10% responses to pH1N1 HA) were seen, whereas significantly greater responses in ≥1 immune compartments were seen to H3N2 and B/Victoria. pH1N1 shedding was not related to pre-existing immunity in 2016–2017. Vaccination with 2017–2018 LAIV showed improvement in pH1N1 shedding with no significant difference between strains: 67.7%, 63.2%, and 68.4% children shedding pH1N1, H3N2, and B/Victoria at day 2 post-LAIV (see Figure 1). This was matched by enhanced pH1N1 HA-specific T-cell responses, with 47.1% children showing a CD4 + IFNg + and 54.4% a CD4 + IL2 + response (see Figure 2). HAI and mucosal IgA data for 2017–2018 are currently being generated and will be presented, as well as key interactions between the parameters measured. Conclusion: Our data suggest that poor pH1N1 A/California strain replication in vivo may explain recent suboptimal LAIV performance and suggest that an improvement can be expected with new pH1N1 strains included in current LAIV formulations. Disclosures: All authors: No reported disclosures.